Remittances, exchange rates and the labor supply of Mexican Migrants in the U.S. - Marc Fox; Oded Stark (Harvard University, Center for Population Studies Cambridge, Massachusetts, 1987)
This paper assumes that migrants derive utility from their own consumption, their own leisure, and remittances to their family. It hypothesizes that the labor supply and remittances of Mexican migrants in the U.S. are jointly determined. Shits in real exchange rates affect the cost of sending a given real volume of remittances back to the family in the sending country. This in turn induces income and substitution effects on both remittances and labor supply. It is argued that the substitution effect would dominate. Therefore, under reasonable conditions, a real depreciation of the peso should lead to an increase in both remittances and labor supply. Empirical work using U.S. Census data and a data set containing information on Mexican migrants in the U.S. lends support to the theoretical predictions.
Keywords: D01; D11; D12; F22; F24; F31; F33; J22; J61; O15; 330; Mexican migrants in the U.S.; Labor supply; Remittances; Exchange rate